Development of Science Education Game Base on Computer Vision for Primary School Student - Budiman, Saiful Nur; Lestanti, Sri; Rahmat, Mohammad Farried; Nafis, Mohamad (LPPM Institut Teknologi Telkom Purwokerto, 2023)
In this research, a discussion was carried out regarding the use of computer vision in educational games developed using the Python programming language and the Mediapipe library. Game applications must be able to capture hand movements and create hand landmark models. These landmarks are used to move the snake's head in the Snake Game and answer questions in the Virtual Quiz. The aim of this research is to develop interest and increase focus in elementary school students with educational games. An analysis was carried out on the results of the respondent's questionnaire to determine the impact of using educational games on students' interest in learning. It was found that 80% of these educational games helped students understand learning concepts. The games developed are also appropriate to the level and knowledge of skills, especially for grade 2 and 3 students with a percentage score of 60%. There are obstacles to the development of this educational game, namely 30% of respondents experiencing difficulties in using it. Sometimes hand movements cannot be captured properly, if the distance of the hand from the camera is too close or far.